The CD20 homolog Ms4a8a integrates pro- and anti-inflammatory signals in novel M2-like macrophages and is expressed in parasite infection - Schmieder, Astrid; Schledzewski, Kai; Michels-Zetsche, Julia D.; Schönhaar, Kathrin; Sauer, Andrea; Sticht, Carsten; Géraud, Cyrill; Goerdt, Sergij (European journal of immunology, 2012)
Recently, we identified the CD20 homolog Ms4a8a as a novel molecule expressed by tumor-associated macrophages that directly enhances tumor growth. Here, we analyzed Ms4a8a+ macrophages in M2-associated infectious pathologies. In late-stage Trypanosoma congolense and Taenia crassiceps infections, Ms4a8a expression was detected in hepatic and peritoneal macrophages respectively. Innate immunity in these infections is modulated by Toll-like receptor (TLR) signaling and TLR2/4/7 agonists strongly induced Ms4a8a expression in bone marrow derived macrophages (BMDMs) treated with M2 mediators (glucocorticoids/IL-4). LPS/dexamethasone/IL-4-induced Ms4a8a+ BMDMs were characterized by strong expression of mRNA of mannose receptor (Mmr), arginase 1, and CD163, and by decreased iNOS expression. Coinduction of Ms4a8a by M2 mediators and TLR agonists involved the classical TLR signaling cascade via activation of MyD88/TRIF and NF-κB. Forced overexpression of Ms4a8a modulated the TLR4 response of RAW264.7 cells as shown by gene expression profiling. Upregulation of Hdc, Tcfec, and Sla was confirmed both in primary LPS/dexamethasone/IL-4-stimulated Ms4a8a+ BMDMs and in peritoneal macrophages from late-stage Taenia crassiceps infection. In conclusion, we show that TLR signaling skews the typical alternative macrophage activation program to induce a special M2-like macrophage subset in vitro that also occurs in immunomodulatory immune reactions in vivo, a process directly involving the CD20 homolog Ms4a8a.